Was I exacting? Sure. Was I occasionally sarcastic? Of course. - Wriston, Walter B. (Tufts Archival Research Center, 2007)
This document was created from the article, "Was I exacting? Sure. Was I occasionally sarcastic? Of course." written by Walter B. Wriston for the June 1987 edition of "Institutional Investor." The original article is located in MS134.003.027.00001.